Control System for Less than Wind Turbines 1500W - Icaza, D.; Pauta, A.; Saguay, G.; Solis, F. (Journal of Technology Innovations in Renewable Energy, 2016)
Using wind power generation is another alternative for remote homes, where there is no electricity grid. Especially in Ecuador there are several places where the wind resource is really stable for the year, though at times the wind regime it becomes turbulent wind speeds become quite high exceeding 12 m / s affecting the wind turbine components. Generally in the Ecuadorian highlands are available permanent winds of medium intensity capable of generating electricity, but by having a system of turbulence for short periods of time it jeopardizes the deployed equipment and therefore the investments made by what this study guarantees the stability of small wind turbines that are very useful in our environment to generate electricity in field type housing shelters.